AB0383 LATENT TUBERCULOSIS INFECTION SHOULD BE MONITORED IN BOTH TUMOR NECROSIS FACTOR INHIBITORS AND NON-TUMOR NECROSIS FACTOR INHIBITORS IN BIOLOGICAL-NAïVE PATIENTS WITH RHEUMATOID ARTHRITIS. (June 2019) - Huang, Yun-Ju; Fang, Yao-Fan; Luo, Shue-Fen; Yu, Kuang-Hui; Kuo, Chang-Fu; Tsai, Ping-Ha; Chen, Yen-Fu
Abstract : Background: The risk of latent tuberculosis infection (LTBI) increased during the treatment of biologic agents for patients with rheumatoid arthritis. Taiwan rheumatology association recommend performing at least annual interferon-gamma release assays (IGARs) testing during biologic treatment course because of the moderate prevalence of tuberculosis in Taiwan.[1] Although increased tuberculosis reactivation rate in patients with TNF inhibitor is reported, the risk of LTBI in patients with RA treated by non-TNF inhibitors is limited. Objectives: The aim is to use serial interferon-gamma release assays (IGRAs) as a diagnostic tool for LTBI in biologic-naïve patients with rheumatoid arthritis treated with TNF and non-TNF inhibitors in Taiwan. Methods: We retrospectively collected 313 biologic-naïve patients with rheumatoid arthritis receiving biologic agents between 2013 to 2017 in Chang Gung Memorial hospital in Taiwan. All RA patients underwent semi-annual IGRA test during biologic agent treatment. Cox proportional hazard model was used for analysis to compared RA patients with TNF and non-TNF inhibitors. Results: The age of patients and disease duration are 55.9 13.1 year-old and 5.2 2.0 years(Table 1). The LTBI rate in patients with rheumatoid arthritis after biologic treatment is 6.7%. Out of the 21 patients with LTBI, 12(6%) patients were treated with TNF inhibitors, 9(8%) patients were treated with non-TNF inhibitors (Figure 1 ). 42.9%(9/21) received chemoprophylactic therapy by isoniazid but no patient suffered from active TB till the end of study period. Patients with TNF inhibitors was associated with a hazard ratio (HR) of 4.43 (95% CI, 0.80-24.39) after adjusted age, sex, diabetes history, prednisolone use and disease duration. This Cox regression analysis of RA patients found that the risk of LTBI was not different in TNF or non-TNF inhibitors. Conclusion: Our study revealed biologic-naïve patients with rheumatoid arthritis have the same risk of LTBI. All RA patients who need either TNF or non-TNF inhibitors should be monitored LTBI in moderate prevalence TB area. References: [1] Chen, Y.-H., 2015 TRA revised recommendations for screening and management of tuberculosis infection in patients before and after anti-tumor necrosis factor-alpha biological treatment. Vol. 29. 2015. 1-8. Disclosure of Interests: None declared